A device for preventing venous stasis - Liew, Ngoh Chin; Lee, Limi (2014)
The present invention relates to a device for preventing venous stasis and the venous thrombosis that might arise due to prolonged immobility. More specifically the present invention is directed to develop a device for inducing stepping like movement in the knee and ankle joint of its user’s feet and thereby contracting the muscles attached with the knee and ankle in the stepping like manner which propels the venous blood upwards for preventing venous stasis and venous thromboembolism comprising foot pedals(4, 6) for cooperatively and releasably securing to the user’s feet and pneumatic driving means(8, 10, 12, 16) operatively connected to said foot pedals(4, 6) to selectively propel each said foot pedal secured to said user’s feet in reciprocating sequence such as to induce stepping movement of the user’s feet. The device is particularly useful in health care industry.